Association of IL-10-promoter genetic variants with the rate of CD4 T-cell loss, IL-10 plasma levels, and breadth of cytotoxic T-cell lymphocyte response during chronic HIV-1 infection. - Naicker, D; Wang, B; Losina, E; Zupkosky, J; Bryan, S; Reddy, S; Jaggernath, M; Mokgoro, M; Goulder, P; Kaufmann, D; Ndung'u, T (2012)
BACKGROUND: Interleukin-10 (IL-10) is a potent immunoregulatory cytokine. IL-10-promoter polymorphisms have been shown to affect human immunodeficiency virus type 1 (HIV-1) clinical outcomes but the underlying mechanisms are poorly understood. METHODS: We investigated the relationship between IL-10-promoter variants, plasma cytokine levels, immune responses and markers of disease outcome in antiretroviral-naïve HIV-1 chronically infected individuals from South Africa. Two IL-10-promoter single nucleotide polymorphisms (SNPs) were genotyped in 451 participants. Baseline plasma levels of select cytokines were measured for 112 individuals. Viral load, CD4(+) T-cell counts and HIV-1-specific interferon-gamma CD8(+) T-cell immune responses were measured at baseline. CD4(+) T-cell counts were measured longitudinally and rates of CD4(+) T-cell decline computed for 300 study subjects. RESULTS: The minor IL-10-1082G and -592A variants occurred at frequencies of 0.31 and 0.34, respectively. The -592AA genotype associated significantly with attenuated loss of CD4(+) T cells (P = .0496). Individuals possessing -1082GG had significantly higher IL-10 levels compared to -1082AA/AG (P = .0006). The -592AA genotype was associated with greater breadth of virus-specific CD8(+) T-cell responses compared to CC and CA (P = .002 and .004 respectively). CONCLUSIONS: IL-10-promoter variants may influence the rate of HIV-1 disease progression by regulating IL-10 levels and the breadth of CD8(+) T-cell immune responses.